A comparative assessment of secondary surgeries between nasoalveolar molding-treated and non nasoalveolar molding-treated patients with unilateral cleft lip and palate - Tulasi Nayak; Bonanthaya Krishnamurthy; Renu Parmar; Pritham N Shetty (Wolters Kluwer Medknow Publications, 2021)
Introduction: Secondary surgeries are a commonly documented element of cleft treatment. It adds to the surgical and economic burden of care. Nasoalveolar molding (NAM) is one of the techniques which has gained popularity as it has proven to reduce the pre surgical severity. NAM has also been proposed to reduce the need for future secondary surgeries. In this retrospective study, we aimed to compare the incidence of secondary surgeries in NAM treated and non-NAM-treated patients with unilateral cleft lip and palate (UCLP). Methods: In this retrospective study, all consecutively treated NAM and non-NAM patients with UCLP who had undergone primary surgeries in 2011-2013 were considered. Only those patients who had a complete clinical and surgical record at 5 years of age were included for this study. Thirty-eight patients in NAM group and 48 patients in non-NAM group were compared. All patients had received the same protocol with the exception of NAM. The cleft severity index was used to check the preoperative cleft severity. The type of lip defect was described for all patients who had received the secondary surgery. Results: Pre NAM clefts were found to be more severe than the non-NAM group. However, after the NAM therapy, the cleft severity was less than the non-NAM group. Non-NAM group had a statistically higher number of lip revision surgeries with a broader variety of defects than the NAM group. There was no statistically significant difference for the Fistula closures. Conclusion: NAM reduced the cleft severity at the pre surgical stage. At 5 years of follow-up, NAM-treated patients had a lower surgical burden of care in comparison to the non-NAM-treated patients.